The role of arbuscular mycorrhizal fungi in nonnative plant invasion along mountain roads. Issue 3 (30th October 2020) - Clavel, Jan; Lembrechts, Jonas; Alexander, Jake; Haider, Sylvia; Lenoir, Jonathan; Milbau, Ann; Nuñez, Martin A.; Pauchard, Anibal; Nijs, Ivan; Verbruggen, Erik
Summary: Plant associated mutualists can mediate invasion success by affecting the ecological niche of nonnative plant species. Anthropogenic disturbance is also key in facilitating invasion success through changes in biotic and abiotic conditions, but the combined effect of these two factors in natural environments is understudied. To better understand this interaction, we investigated how disturbance and its interaction with mycorrhizas could impact range dynamics of nonnative plant species in the mountains of Norway. Therefore, we studied the root colonisation and community composition of arbuscular mycorrhizal (AM) fungi in disturbed vs undisturbed plots along mountain roads. We found that roadside disturbance strongly increases fungal diversity and richness while also promoting AM fungal root colonisation in an otherwise ecto‐mycorrhiza and ericoid‐mycorrhiza dominated environment. Surprisingly, AM fungi associating with nonnative plant species were present across the whole elevation gradient, even above the highest elevational limit of nonnative plants, indicating that mycorrhizal fungi are not currently limiting the upward movement of nonnative plants. We conclude that roadside disturbance has a positive effect on AM fungal colonisation and richness, possibly supporting the spread of nonnative plants, but that there is no absolute limitation of belowground mutualists, even at high elevation. Abstract : See also the Commentary on this article by Bueno et al., 230 : 883–885 .